Cancer risk and mortality among firefighters: a meta-analytic review - Lee, David J.; Ahn, Soyeon; McClure, Laura A.; Caban-Martinez, Alberto J.; Kobetz, Erin N.; Ukani, Henna; Boga, Devina J.; Hernandez, Diana; Pinheiro, Paulo S. (Frontiers in Oncology, 2023)
Background Firefighting is a hazardous occupation that is associated with an increased risk of select cancers. The number of studies has grown in recent years allowing for a synthesis of findings. Methods Following PRISMA guidelines, multiple electronic databases were searched to identify studies on firefighter cancer risk and mortality. We computed pooled standardized incidence risk (SIRE) and standardized mortality estimates (SMRE), tested for publication bias, and conducted moderator analyses. Results Thirty-eight studies published between 1978 and March 2022 were included for final meta-analysis. Overall, cancer incidence and mortality were significantly lower for firefighters (SIRE = 0.93; 95% CI: 0.91-0.95; SMRE = 0.93; 95% CI: 0.92 - 0.95) compared to the general population. Incident cancer risks were significantly higher for skin melanoma (SIRE = 1.14; 95% CI:1.08 - 1.21), other skin cancers (SIRE = 1.24; 95% CI:1.16-1.32), and prostate cancer (SIRE = 1.09; 95% CI: 1.04-1.14). Firefighters showed higher mortality for rectum (SMRE = 1.18; 95% CI: 1.02-1.36), testis (SMRE = 1.64; 95% CI: 1.00-2.67), and non-Hodgkin lymphoma (SMRE = 1.20; 95% CI: 1.02-1.40). There was evidence of publication bias for SIRE and SMRE estimates. Some moderators explained variations in study effects, including study quality scores. Conclusions Firefighters are at higher risk for several cancers; to the extent that some (e.g., melanoma and prostate) are screening amenable, more study into firefighter-specific recommendations for cancer surveillance is needed. Moreover, longitudinal studies with more detailed data on the specific length and types of exposures are necessary, as well as on unstudied subtypes of cancers (e.g., subtypes of brain cancer and leukemias) are needed.